Apelin and Apelin Receptor in Follicular Granulosa Cells of Buffalo Ovaries: Expression and Regulation of Steroidogenesis - Shokrollahi, Borhan; Zheng, Hai-Ying; Li, Ling-Yu; Tang, Li-Ping; Ma, Xiao-Ya; Lu, Xing-Rong; Duan, An-Qin; Zhang, Yu; Tan, Xiao-Hui; Huang, Chen-Xi; Xu, Yuan-Yuan; Shang, Jiang-Hua (Frontiers in Endocrinology, 2022)
Apelin (APLN), as a ligand for APJ (an orphan G-protein coupled receptor), is an adipokine with pleiotropic effects in many physiological processes of the body. It has an important role function in the control of reproduction particularly in females (mainly in control of ovarian function). This study was carried out to investigate the mRNA and protein amounts of APLN/APJ in granulose cells (GCs) of ovarian follicles with small (SF), medium (MF), and large (LF) sizes of buffalo (Bubalus bubalis) and the effect of IGF1 and FSH on the expression levels of APLN/APJ. In addition, we evaluated the effect of various doses of APLN (isoforms -13 and -17) singly or in combination with IGF1 and FSH on estradiol (E2) and progesterone (P4) secretion in GCs. The mRNA and protein abundance of APLN was the highest in GCs of LF while the APJ expression enhanced with follicle enlargement in GCs (p-value<0.01). IGF1 and FSH elevated the mRNA and protein amounts of APLN and FSH, and IGF1 increased the expression of APJ in buffalo GCs (p-value<0.01). Both isoforms of APLN (-13/-17) singly or in the presence of IGF1 or FSH increased the secretion of E2 and P4 with or without preincubation of cells with APJ antagonist (ML221 10 µM), although we had some variation in the effects. Concurrently, APLN-13/-17 significantly increased mRNA and protein expression of CYP19A1 and StAR (p-value<0.01). ML221 substantially diminished the secretion of E2 and P4 and also the expression of CY19A1 and StAR in buffalo GCs (p-value<0.01). We also revealed that APLN-13/-17 (10-9 M), singly or in response to IGF1 and FSH increased the production of E2 and P4 in different times of stimulation. In conclusion, APLN may play a crucial role in steroidogenesis and follicular development in ovarian GCs of buffalo.